What do school principals do? Leadership practices in Spain drawn from PISA and TALIS international studies - Izquierdo Gómez, David (Revista Complutense de Educación, 2015)
Principals play a key role in schools. Their actions affect the efficacy of schools and indirectly on the students’ academic performance. Numerous studies describe the different activities that principals perform in their daily practice, grouping them in dimensions, not existing unanimity neither around the practices carried out nor the dimensions. In Spain, the new educational law, LOMCE, emphasizes the importance of looking into what international research says regarding the field of education to support the need for change and justify the ones that are being made, and develops an extended list of competences of the principal. This study is a synthesis of a narrative research with the following analysis unit: the results of the PISA (Programme for International Student Assessment) and TALIS (Teaching and Learning International Study) international reports, and the data provided on school leadership and their practices, from which conclusions are inferred, comparing them with the competences stated in the LOMCE. The comparative analysis of the leadership practices presented depicts a still uneven and heterogeneous scenario, not existing agreement neither for the setting of boundaries for the leadership dimensions, nor for the number of practices that constitute them. Such a scenario points towards the need for further empirical research, in order to accurately obtain a homogeneous catalogue of the actions carried out by principal, that may open the door to the development of the role of principal, and to the improvement of effectiveness and performance of schools, as it is suggested internationally, and it is an objective of the new educational law.